Spiritual Care Education of Health Care Professionals - Donia Baldacchino (Religions, 2015)
Nurses and health care professionals should have an active role in meeting the spiritual needs of patients in collaboration with the family and the chaplain. Literature criticizes the impaired holistic care because the spiritual dimension is often overlooked by health care professionals. This could be due to feelings of incompetence due to lack of education on spiritual care; lack of inter-professional education (IPE); work overload; lack of time; different cultures; lack of attention to personal spirituality; ethical issues and unwillingness to deliver spiritual care. Literature defines spiritual care as recognizing, respecting, and meeting patients’ spiritual needs; facilitating participation in religious rituals; communicating through listening and talking with clients; being with the patient by caring, supporting, and showing empathy; promoting a sense of well-being by helping them to find meaning and purpose in their illness and overall life; and referring them to other professionals, including the chaplain/pastor. This paper outlines the systematic mode of intra-professional theoretical education on spiritual care and its integration into their clinical practice; supported by role modeling. Examples will be given from the author’s creative and innovative ways of teaching spiritual care to undergraduate and post-graduate students. The essence of spiritual care is being in doing whereby personal spirituality and therapeutic use of self contribute towards effective holistic care. While taking into consideration the factors that may inhibit and enhance the delivery of spiritual care, recommendations are proposed to the education, clinical, and management sectors for further research and personal spirituality to ameliorate patient holistic care.